Immobilization of bovine serum albumin (BSA) and hepatitis B core antigen (HBcAg) on optical fiber core surface - Basri, Ameliawati (2015)
Hepatitis B virus (HBV) infections are one of the major worldwide health problems. Since the conventional laboratory diagnostics tool can be time consuming and laborious, the development of a biosensor with higher sensitivity and specificity in detecting the disease is crucial. For our future development of a new HBV biosensor, the hepatitis B core antigen (HBcAg) was selected to be immobilized on the optical fiber core surface. Techniques of immobilization involved in this project were physical adsorption of HBcAg on the core surface of the optical fiber and chemical modification of the core surface with the application of glutaraldehyde (GTA) as a crosslinker. Apart from that, optimization work were also carried out by using a model protein bovine serum albumin (BSA) with several parameters namely incubation time, amount of protein, concentration and type of washing agents. The coating on the core surface of the optical fiber will induce a light signal which will be analyzed by the Optical Spectrum Analyser (OSA). The wavelength and the optical power of each coating reagent at each stage of immobilization will determine the light transmission signal. Transmission signal is the determinant factor of the immobilization rate of the protein on the optical fiber core surface. Based on the OSA measurement and microscopic observation that were carried out in this project, BSA and HBcAg were successfully immobilized on the tapered optical fiber core surface by using chemical modification method. The immobilization rate of both proteins using chemical modification is about 98% and this is due to the application of strong and stable crosslinker, glutaraldehyde which provided a covalent link of the proteins to the optical fiber core surface. It was also determined that uniform coating should be maintained through the experiment to avoid light losses that will affect the transmission signal. This early development of the optical fiber-based biosensor gave a promising future and able to improve the current laboratory diagnostic tools. Further and continuous improvement shall be carried out to test its sensitivity and stability of the biosensor.